2014
DOI: 10.3174/ajnr.a4072
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Fiber Tracking in Early Acquired Brain Injury Causing Cerebral Palsy

Abstract: BACKGROUND AND PURPOSE: Diffusion-weighted MR imaging and fiber tractography can be used to investigate alterations in white matter tracts in patients with early acquired brain lesions and cerebral palsy. Most existing studies have used diffusion tensor tractography, which is limited in areas of complex fiber structures or pathologic processes. We explored a combined normalization and probabilistic fiber-tracking method for more realistic fiber tractography in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
13
0
1
Order By: Relevance
“…Hoon et al (2002, 2009) found that the severity of injury in the thalamocortical sensory pathways correlated to the severity of deficits in sensorimotor function in children with CP born preterm. Similarly, abnormalities assessed using DTI in preterm infants were seen in both CST and thalamocortical projections to the somatosensory cortex, and both tracts were associated with underlying pathology on conventional MRI (Lennartsson et al, 2015). …”
Section: Brain Injury In Cerebral Palsymentioning
confidence: 99%
“…Hoon et al (2002, 2009) found that the severity of injury in the thalamocortical sensory pathways correlated to the severity of deficits in sensorimotor function in children with CP born preterm. Similarly, abnormalities assessed using DTI in preterm infants were seen in both CST and thalamocortical projections to the somatosensory cortex, and both tracts were associated with underlying pathology on conventional MRI (Lennartsson et al, 2015). …”
Section: Brain Injury In Cerebral Palsymentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) can evaluate structural connectivity by examining the direction and intensity of water diffusion in white matter tracts to reveal the characteristics of tissue microstructure, facilitating the study of sensory pathways [Lai et al, 2014]. Multiple DTI studies evaluating the corticospinal tract after perinatal stroke [van der Aa et al, 2013;Jaspers et al, 2015;Lennartsson et al, 2015;Roze et al, 2012] have defined imaging biomarkers associated with clinical outcome such as decreased fractional anisotropy (FA) in the lesioned hemisphere. Whether diffusion imaging of sensory pathway structural connectivity carries the same potential has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional anisotropy (FA) is a commonly investigated biomarker of such diffusion and tissue microstructure, where greater values indicate more ordered diffusion along white matter tracts. Several studies in children with hemiparesis have demonstrated that reduced FA, indicative of more random diffusion within the stroke‐affected CST, is associated with poor motor function in the contralateral, affected limbs (van der Aa et al, ; Lennartsson et al, ; Roze et al, ; Yoshida et al, ). More recently, we have investigated the relationship between sensory dysfunction (Kuczynski, Dukelow, Semrau, & Kirton, ; Kuczynski, Semrau, Kirton, & Dukelow, ) and diffusion properties of the dorsal column medial lemniscus sensory pathways in children with perinatal stroke and hemiparetic CP (Kuczynski et al, ).…”
Section: Introductionmentioning
confidence: 99%